PATHOLOGICAL CHANGES INDUCED IN MICE DUE TO EXPERIMENTAL INFECTION OF CANINE HOOKWORM LARVAE - C. H. KRISHNABHANU; VARDHANI, V. VIVEKA (The Bioscan, 2013)
Four groups of each mice were infected orally with a single dose of 500 (group A), 1000 (group B), 2000 (group C) and 4000 (group D) third stage, infective larvae of Ancylostoma caninum. A single group (E) of mice was kept as uninfected control for comparison. The survival pattern of larvae and/or the pathogenic reaction in small intestine of different experimental groups of mice occurred in a dose dependent manner. The rapid termination/ expulsion of A. caninum larvae from the experimental mouse of gastrointestinal tract is associated with a marked accumulation of various types of white cells in the mucosa of bowel. The persistence of A. caninum larvae in abdominal muscles of mice (in groups A, B, C and D) triggered the immune response thereby causing diffuse infiltration of inflammatory cells. Muscle fibers showed increase in the number of sarcolemmal nuclei on day 9,16 and 30 of infection in groups A and B and degeneration in groups C and D (on day 4) of infection.